1990
DOI: 10.1002/mrm.1910130112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation in blood and blood clots

Abstract: Nuclear magnetic relaxation rates are measured for whole blood, blood plasma, whole blood clots, and plasma clots in vitro. Relaxation rates are linear in the hematocrit and transverse relaxation rates are significantly greater than longitudinal relaxation rates. Longitudinal relaxation rates measured from 0.01 to 42 MHz for proton Larmor frequencies are found to decline monotonically with increasing magnetic field strength; however, the dispersion curves do not follow a simple Lorentzian behavior, which is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 29 publications
10
126
1
Order By: Relevance
“…T2-relaxation-under-spin-tagging MRI estimates global Yv through its effects on the T2-relaxation time in a large intracranial venous sinus (i.e., superior sagittal sinus). The T2-relaxation time is more accurate than T2* regarding their interrelationship with blood oxygenation (Bryant et al, 1990;Gomori et al, 1987;Thulborn et al, 1982;Wright et al, 1991) with high degree of precision and reliability. The Yv converted from T2 using TRUST has been shown in good agreement with PET studies .…”
Section: Discussionmentioning
confidence: 99%
“…T2-relaxation-under-spin-tagging MRI estimates global Yv through its effects on the T2-relaxation time in a large intracranial venous sinus (i.e., superior sagittal sinus). The T2-relaxation time is more accurate than T2* regarding their interrelationship with blood oxygenation (Bryant et al, 1990;Gomori et al, 1987;Thulborn et al, 1982;Wright et al, 1991) with high degree of precision and reliability. The Yv converted from T2 using TRUST has been shown in good agreement with PET studies .…”
Section: Discussionmentioning
confidence: 99%
“…The relatively long TR of 3000 msec was chosen to minimize T 1 effects in arteries since this would compromise measurement of the ratio of signal intensity change between tissue and artery. The T 1 of blood before administration of contrast is approximately 1 sec (35), so that the TR of 3000 ms, at 3 times that value, should avoid significant T 1 -shortening effects of the contrast agent and produce mainly T* 2 effect. In support of this, preliminary studies (data not shown) of S 0 vs. TR showed that relative baseline signal of blood vessels without any contrast reached a maximum at or just above 2500 msec.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained and processed the images per Oguz et al, but substituted specific values for the spin-lattice relaxation time (T1) of blood at 1.5 T based on packed-cell volume (PCV). 11,12 The vascular distributions of the major cerebral arteries 13 were independently outlined by 2 investigators and used to calculate regional CBF to gray matter. Blood studies, including PCV, white blood cell (WBC) count, and platelet count, were performed using an automated analyzer (Sysmex SE 9500; Roche, Indianapolis, IN) when the patients were in their usual state of health.…”
Section: Study Proceduresmentioning
confidence: 99%